Treated nanolayered Mn oxide by potassium fluoride: An improvement for nanolayered Mn oxide toward water oxidation. (14th December 2016) - Najafpour, Mohammad Mahdi; Hosseini, Seyedeh Maedeh; Zarei Ghobadi, Mohadeseh; Rafighi, Parvin; Bagheri, Robabeh; Song, Zhenlun
Abstract: Water splitting can store sustainable energies in the form of fuel (H2 ) and oxidant (O2 ). However, the efficiency of H2 production from the reaction is limited by the slow kinetics of the water oxidation. Herein the promising role of fluoride on water-oxidizing activity of nanolayered Mn oxide is reported. The effects were studied for water oxidation in the presence of cerium(IV) ammonium nitrate. These experiments showed that the treatment of nanolayered Mn oxide by potassium fluoride increases water-oxidizing activity of these oxides in the presence of cerium(IV) ammonium nitrate approximately two times. Graphical abstract: We showed that the treatment of nanolayered Mn oxide by potassium fluoride increases water-oxidizing activity of these oxides in the presence of cerium(IV) ammonium nitrate approximately two times. Highlights: Hydrogen production by water splitting is a very promising way to store sustainable energies. Nanolayered Mn oxide is highly attractive as catalysts for water oxidation. The treatment of nanolayered Mn oxide by KF increases water-oxidizing activity of these oxides.